1996
DOI: 10.1111/j.1432-1033.1996.0692h.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Subsites on the Active Center of Pig Kidney Trehalase

Abstract: A kinetic analysis of the active site of pig kidney trehalase was made by examining two types of inhibitors that are monosaccharide analogs and cause a Competitive inhibition of the trehalase. Trehalase hydrolyzes trehalose (a-D-glyCopyranoSyl a-D-glucopyranoside) to give an equimolar mixture of a-Dglucose and, by inversion of configuration, P-D-glUCOse. 1,4-Dideoxy-l,4-imino-D-arabinito1 is considered to be a transition state (glucosyl cation) analog, while methyl P-D-glucoside, 1,5-dideoxy-1,5-iminO-Dglucito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
24
0
2
Order By: Relevance
“…[10,11] Trehalases are inverting glycosidases; this suggests the presence of a catalytic acid group, together with a nucleophilic water molecule, in the active site of the enzyme. [12] Kinetic studies performed with porcine kidney trehalase in the presence of two types of competitive inhibitors [13] support the earlier hypothesis [14] that the active center of the enzyme may comprise two subsites, one for catalysis and one for recognition, acting separately on each glucose unit of trehalose. This conclusion could probably be extended to other trehalases.…”
supporting
confidence: 55%
“…[10,11] Trehalases are inverting glycosidases; this suggests the presence of a catalytic acid group, together with a nucleophilic water molecule, in the active site of the enzyme. [12] Kinetic studies performed with porcine kidney trehalase in the presence of two types of competitive inhibitors [13] support the earlier hypothesis [14] that the active center of the enzyme may comprise two subsites, one for catalysis and one for recognition, acting separately on each glucose unit of trehalose. This conclusion could probably be extended to other trehalases.…”
supporting
confidence: 55%
“…Final catalytic hydrogenation afforded compound 11. Due to the reported activity against trehalases of some iminofuranoses, such as compound 8 [11] (Figure 1), we envisaged the possibility to expand our set of potential inhibitors also to pseudodisaccharides obtained by CM of C-allyl-iminofuranoses. Two different allyl-iminofuranoses were synthesized and used for the CM reaction (Scheme 4), pos- The synthesis of α-C-allyl iminoarabinofuranosyl derivative 24 (Scheme 4A) proceeded by Grignard addition to nitrone 28, [19] as recently described.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, a few iminosugar-based compounds (such as 4-8, Figure 1) have been also proposed as trehalase inhibitors. [5,11,12] [a] Department of Biotechnology and Biosciences,tected allyl C-iminoglycosides as the key step in homo-or heterodimerization reactions. The target products, obtained with the CM reaction, were fully hydrogenated by catalytic hydrogenolysis, and preliminary biological screening of the products as inhibitors of commercially available porcine trehalase was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was also reported that pyrrolidine derivatives (i.e., DAB-1, 9 , Fig. 2) [19] may act as trehalase inhibitors, in particular as competitive inhibitors with affinity to the catalytic site [19]. In general, it is well known that a key issue in the design of glycosidase inhibitors is specificity, for example, 1-deoxynojirimycin ( 7 ) is a glycosidase inhibitor in the low micromolar range, but despite its activity it lacks specificity.…”
Section: Resultsmentioning
confidence: 98%